Corvis ST Tonometer for Measuring Postoperative IOP in LASIK Patients. Issue 5 (May 2015) - Hong, Jiaxu; Yu, Zhiqiang; Jiang, Chunhui; Zhou, Xingtao; Liu, Zuguo; Sun, Xinghuai; Xu, Jianjiang
ABSTRACT: Purpose: To compare the postoperative measurements of intraocular pressure (IOP) using the Corvis ST Tonometer (CST), ocular response analyzer (ORA), and Goldmann applanation tonometry (GAT) in eyes undergoing laser in situ keratomileusis (LASIK), as well as to analyze the relationship between the corneal biomechanical parameters of the CST and the ORA. Methods: Fifty participants who had undergone LASIK to treat myopia in the previous 3 months were enrolled. Postoperative IOP measurements of these participants were obtained using the CST, ORA (corneal-compensated IOP [IOPcc], Goldmann-correlated IOP [IOPg]), and GAT. Device agreement was calculated by Bland-Altman analysis. The metrics of corneal biomechanical properties were recorded using the ORA and the CST. Corneal biomechanical parameters were compared. Results: The Bland-Altman analysis revealed a significant bias between CST and GAT, between CST and IOPcc, and between CST and IOPg of 3.4, 1.0, and 3.8, mm Hg, respectively, with 95% limits of agreement of −0.7 to 7.5 mm Hg, −2.1 to 4.2 mm Hg, and −0.4 to 8.0 mm Hg. The ORA-derived IOP measurements, CST-derived IOP, and GAT IOP values showed good correlation with each other. The CST IOP and IOPcc were higher than the GAT IOP (all p < 0.05), whereas IOPg did not differ from the GAT IOP readings. Ocular response analyzer–derived corneal biomechanical parameters (corneal hysteresis and the corneal resistance factor) showed significant correlations with CST-derived parameters, including the maximum deformation amplitude at the corneal apex and the time from start until the first applanation. Conclusions: The CST offers an alternative method for measuring postoperative IOP in LASIK patients, and it appears to obtain higher IOP values than other tonometry techniques. The technique may facilitate the investigation of corneal biomechanical property changes in LASIK-treated eyes.